In vivo hematopoietic stem cell transduction - Richter, Maximilian (Hematol Oncol Clin North Am, 2017)
Current hematopoietic stem cell (HSC) gene therapy approaches rely on the collection of patient HSCs, followed by their culture and expansion in vitro, their modification using γ-retrovirus or lentiviral vectors, and their re-infusion into myelo-conditioned patients. While this approach has been successfully used in numerous clinical trials, its reliance on the extended ex vivo culture of patient HSCs comes with a set of disadvantages. Culturing HSCs in the presence of a cytokine cocktail to facilitate their expansion and transduction is thought to negatively impact the long-term viability of HSCs, and their homing and repopulation capacity. Importantly, the requirement for myeloablative regimens in patients represents a critical risk factor and results in considerable morbidity. In addition to these biological problems, the process of ex vivo HSC manipulation is also challenging from a logistics and regulatory standpoint, as manipulations must be performed in specialized, accredited centers. These complexities lead to a high price of such gene therapeutic regimens, and subsequently severely limited patient access to these treatments. In vivo HSC gene therapy approaches aim to simplify the gene therapy process by eliminating the need for ex vivo handling of patient HSCs. The in vivo approach can be subdivided into three methods. One method is based on the direct modification of HSCs in the bone marrow following intraosseous injection. Another involves intravenous injection of gene delivery vectors that home to HSCs in bone marrow. We have developed an alternative approach in which HSCs from the bone marrow are mobilized into peripheral blood, become gene modified upon intravenous vector administration, and then re-engraft in the bone marrow. We will provide examples of these three approaches and then discuss the advantages and disadvantages of in vivo HSC gene therapy.